Efficient synthesis of diphenyl carbonate from dibutyl carbonate and phenol using square-shaped Zn–Ti–O nanoplates as solid acid catalysts. Issue 103 (6th October 2015) - Wang, Peixue; Liu, Shimin; Zhou, Feng; Yang, Benqun; Alshammari, Ahmad S.; Deng, Youquan
Abstract : Efficient synthesis of diphenyl carbonate from dibutyl carbonate and phenol using square-shaped Zn–Ti–O nanoplates as solid acid catalyst. Abstract : Square-shaped Zn/Ti oxides were prepared by a co-precipitation method and used for the synthesis of diphenyl carbonate (DPC) via transesterification of dibutyl carbonate (DBC) with phenol. The results showed that a 51% yield of butyl phenyl carbonate (BPC) and 13% yield of DPC could be achieved at 205 °C in the presence of 3ZnTi-400 (Zn : Ti molar ratio 3 : 1). Moreover, it is found that 3ZnTi-400 was also an active catalyst for the disproportionation of BPC to DPC, and 80% conversion of BPC was obtained at 190 °C. The prepared catalysts could be reused for three runs of the transesterification without noticeable deactivation. The catalysts were characterized by XRD, SEM, XPS, and TPD with the aim of establishing the relationship between catalytic performance and structure.